'Voorlopig in alle stilte' terwerkstelling van politieke gevangenen in de mijn Willem-Sophia te Spekholzerheide (1945-1946) - Schoot Uiterkamp, Annet (Studies over de sociaaleconomische geschiedenis van Limburg, 2017)
'For the time being keep it silent'. Employment of political prisoners at the mine Willem-Sophia in Spekholzerheide (1945-1946)'.  This article investigates the beginnings of the employment of collaborationist prisoners in Dutch coal mines after the Second World War, especially in the mine Willem-Sophia in Spekholzerheide (1945-1946). Such employment, made urgent by shortage of fuel as well as of labour, was debated in the early months of 1945. Initially the military commander in charge (‘Militair Gezag’) forbade employment of prisoners unless no regular unemployed were available. Mine directors insisted, particularly because in the months following the liberation of the southern part of Limburg, political prisoner camps housed numerous skilled miners. In collective memory their employment is supposed to have generated much resistance among miners and their unions, as it was supposed to be a degradation of their profession. But research in the archives does not produce much evidence to corroborate this as far as the Willem-Sophia is concerned: the first Dutch coal mine to employ these ‘infected’ miners.